Research protocol of the Laval-ROSA Transilab: a living lab on transitions for people living with dementia - Isabelle Dufour; Geneviève Arsenault-Lapierre; Maxime Guillette; Nathalie Dame; Marie-Eve Poitras; Marie-Thérèse Lussier; Annie Fortier; Julie Brunet; Julie Martin; Micheline Laverdure; Ginette Brousseau; Howard Bergman; et al. (BMC, 2023)
Abstract Background The Laval-ROSA Transilab is a living lab that aims to support the Laval Integrated Health and Social Services Centres (Quebec, Canada) in consolidating the Quebec Alzheimer Plan. It aims to improve care transitions between different settings (Family Medicine Groups, home care, and community services) and as such improve the care of people living with dementia and their care partners. Four transition-oriented innovations are targeted. Two are already underway and will be co-evaluated: A) training of primary care professionals on dementia and interprofessional collaboration; B) early referral process to community services. Two will be co-developed and co-evaluated: C) developing a structured communication strategy around the dementia diagnosis disclosure; D) designation of a care navigator from the time of dementia diagnosis. The objectives are to: 1) co-develop a dashboard for monitoring transitions; 2) co-develop and 3) co-evaluate the four targeted innovations on transitions. In addition, we will 4) co-evaluate the impact and implementation process of the entire Laval-ROSA Transilab transformation, 5) support its sustainability, and 6) transfer it to other health organizations. Methods Multi-methods living lab approach based on the principles of a learning health system. Living labs are open innovation systems that integrate research co-creation and knowledge exchange in real-life settings. Learning health systems centers care improvement on developing the organization's capacity to learn from their practices. We will conduct two learning cycles (data to knowledge, knowledge to practice, and practice to data) and involve various partners. We will use multiple data sources, including health administrative databases, electronic health records data, surveys, semi-structured interviews, focus groups, and observations. Discussion Through its structuring actions, the Laval-ROSA Transilab will benefit people living with dementia, their care partners, and healthcare professionals. Its strategies will support sustainability and will thus allow for improvements throughout the care continuum so that people can receive the right services, at the right time, in the right place, and from the right staff.